Efficient and Stable Perovskite Solar Cells with a High Open‐Circuit Voltage Over 1.2 V Achieved by a Dual‐Side Passivation Layer. Issue 41 (11th September 2022) - Kim, Ju‐Hyeon; Kim, Yong Ryun; Kim, Juae; Oh, Chang‐Mok; Hwang, In‐Wook; Kim, Jehan; Zeiske, Stefan; Ki, Taeyoon; Kwon, Sooncheol; Kim, Heejoo; Armin, Ardalan; Suh, Hongsuk; et al.
Abstract: Suppressing nonradiative recombination at the interface between the organometal halide perovskite (PVK) and the charge‐transport layer (CTL) is crucial for improving the efficiency and stability of PVK‐based solar cells (PSCs). Here, a new bathocuproine (BCP)‐based nonconjugated polyelectrolyte (poly‐BCP) is synthesized and this is introduced as a "dual‐side passivation layer" between the tin oxide (SnO2 ) CTL and the PVK absorber. Poly‐BCP significantly suppresses both bulk and interfacial nonradiative recombination by passivating oxygen‐vacancy defects from the SnO2 side and simultaneously scavenges ionic defects from the other (PVK) side. Therefore, PSCs with poly‐BCP exhibits a high power conversion efficiency (PCE) of 24.4% and a high open‐circuit voltage of 1.21 V with a reduced voltage loss (PVK bandgap of 1.56 eV). The non‐encapsulated PSCs also show excellent long‐term stability by retaining 93% of the initial PCE after 700 h under continuous 1‐sun irradiation in nitrogen atmosphere conditions. Abstract : New synthesized non‐conjugated polyelectrolyte is introduced as an interfacial layer between the charge‐transport layer and perovskite absorbent, which significantly reduce both bulk and interfacial nonradiative recombination losses, but also aligns the interface's energy level. The modified perovskite solar cells show a power conversion efficiency of 24.4% (open‐circuit voltage 1.21 V) with negligible hysteresis and superior operational stability.